The Power of Inherited Language in Multilingual Adults. Survey Study - Loewe, Iwona (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
The considerations in this article are focused on the phenomenon of widespread multilingualism in Europe and the increasing number of multilingual adults. A language biography was used as a research tool to access languages in dreams, prayer and thought. The study was conducted on 68 multilingual people. The following results were obtained: regardless of the bilinguals’ age and country of residence, inheritance languages appear in the majority of the respondents (50/68) in dreams. An even greater proportion in favour of inheritance languages was observed in relation to the language of prayer or thought (50/60). The study confirms the hypothesis that inheritance language is a reservoir of childhood experiences and resurfaces actively in emotional and personal activities performed by bilinguals.